2020
DOI: 10.3390/app10238357
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil-Structure Interaction on the Seismic Response of Existing Low and Mid-Rise RC Buildings

Abstract: Reconnaissance studies performed after destructive earthquakes have shown that seismic performance of existing buildings, especially constructed on weak soils, is significantly low. This situation implies the negative effects of soil-structure interaction on the seismic performance of buildings. In order to investigate these effects, 40 existing buildings from Turkey were selected and nonlinear models were constructed by considering fixed-base and stiff, moderate and soft soil conditions. Buildings designed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…For example, a study on instrumented buildings in California (USA) showed that the torsional responses of the supporting structure and/or the in-plane flexibility of floor diaphragms can increase by not negligible factors the seismic-induced force demands on elastic acceleration-sensitive non-structural components . Similarly, it is known that soil-structure interaction (SSI) can affect the acceleration response of the buildings (e,g, Karapetrou et al, 2015;Karatzetzou et al, 2015;de Silva et al, 2019;Fathi et al, 2020;Oz et al, 2020, Hamidia et al, 2021Brunelli et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study on instrumented buildings in California (USA) showed that the torsional responses of the supporting structure and/or the in-plane flexibility of floor diaphragms can increase by not negligible factors the seismic-induced force demands on elastic acceleration-sensitive non-structural components . Similarly, it is known that soil-structure interaction (SSI) can affect the acceleration response of the buildings (e,g, Karapetrou et al, 2015;Karatzetzou et al, 2015;de Silva et al, 2019;Fathi et al, 2020;Oz et al, 2020, Hamidia et al, 2021Brunelli et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ref. [21] investigated the effects of SSI on several residential RC buildings with different capacity design principles founded on four different soil conditions and applying 20 acceleration records. Furthermore, Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The seismic behavior of a building is directly related to the interaction between the three interconnected systems, which are superstructure, foundation and soil medium surrounding the foundation system [1]. The most significant increase in drift demands occurred in first stories and the results corresponding to fixed-base, stiff and moderate cases are closer to each other with respect to soft soil cases [2] indicated that effect of soil-structure interaction on the seismic performance of new buildings is limited with respect to old buildings [3] examined the seismic performance of empirical buildings with SSI [4] and showed that the seismic performance of buildings varied significantly depending on the soil conditions. The site amplification values estimated by considering the local depth of the bedrock surface layer were generally smaller than the seimic accelaration amplification values from the Indonesian seismic building code 1726-2012, there appears to exist a tendency of lower levels of amplification mean regression, in particular for the soft soil site class according to Delfebriyadi et al [5].…”
Section: Introductionmentioning
confidence: 99%